Foreword - Wayne L. Townsend (Washington University Law Quarterly, 1949)
After a lapse of seven years covering the period of World War II and its aftermath, the Washington University Law Quarterly resumes publication with this issue. The Faculty of the School of Law envisage the role of a law review as involving two principal functions: first, as an aid to the busy practitioner and, second, as a medium of student expression with the concomitant training and experience in research.
Keywords: Arbitration and award; Collective bargaining; Labor law